2014
DOI: 10.1186/s13054-014-0587-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of pulse pressure variations for predicting fluid responsiveness in mechanically ventilated intensive care unit patients: the grey zone approach

Abstract: IntroductionPulse pressure variation (PPV) has been shown to predict fluid responsiveness in ventilated intensive care unit (ICU) patients. The present study was aimed at assessing the diagnostic accuracy of PPV for prediction of fluid responsiveness by using the grey zone approach in a large population.MethodsThe study pooled data of 556 patients from nine French ICUs. Hemodynamic (PPV, central venous pressure (CVP) and cardiac output) and ventilator variables were recorded. Responders were defined as patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
86
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(95 citation statements)
references
References 58 publications
1
86
1
5
Order By: Relevance
“…Although Monnet et al (31) showed that the low ability of ΔPP to predict FR was related to low Crs (= 1 / E RS ), others failed to demonstrate any such effect (22,32). These contradictory findings can be explained by partitioning E RS into its lung and chest wall components.…”
Section: Discussionmentioning
confidence: 73%
“…Although Monnet et al (31) showed that the low ability of ΔPP to predict FR was related to low Crs (= 1 / E RS ), others failed to demonstrate any such effect (22,32). These contradictory findings can be explained by partitioning E RS into its lung and chest wall components.…”
Section: Discussionmentioning
confidence: 73%
“…All protective ventilation strategies are associated with low tidal volumes (and the frequently associated application of a high respiratory rate). Therefore, protective ventilation impairs the predictive performance of PPV [4][5][6]9], as it exposes to false negative cases [7,8,16]. Conflicting data were reported when a low tidal volume without high respiratory rate was applied [17].…”
Section: Large Observational Studies Assessing the Validity Of Ppv Inmentioning
confidence: 78%
“…In conclusion, if the problem is fluid resuscitation, functional hemodynamic monitoring using dynamic parameters would be the correct option, taking into consideration the limits to which patients should be sedated, paralyzed, mechanically ventilated, with sinus rhythm and closed chest, no severe pulmonary hypertension or severe right ventricular failure [38][39][40][41]. In mechanically ventilated patients, as well as in spontaneous breathing patients, other types of dynamic parameters can be employed, namely those obtained during a passive leg raising maneuver (PLR): direct measurements of the SV or CO variations, or measurements of surrogates such as descending aortic blood flow changes [42,43].…”
Section: How Do the Parameters Provided By Hemodynamic Monitoring Helmentioning
confidence: 99%